Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2019
DOI: 10.1016/j.chempr.2019.06.023
|View full text |Cite
|
Sign up to set email alerts
|

Sulfate-Templated 2D Anion-Layered Supramolecular Self-Assemblies

Abstract: Tripodal N-methylated(1,3,5-benzene-tricarboxamide)-tris(phenylurea) BTA ligands, possessing urea functionalities in the meta position, are able to form extended self-assembly 2D networks via hydrogen bonding templated by sulfate (SO 4 2À ). Studies in solution and in the solid state, as well as scanning electron microscopy (SEM) on the self-assembly properties of the ligands showed that the convergence also leads to the formation of hierarchical structures, including porous films and spherical nano-sized part… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 32 publications
(22 citation statements)
references
References 38 publications
0
22
0
Order By: Relevance
“…42 More recently, tripodal Nmethylated(1,3,5-benzene-tricarboxamide)-tris(phenylurea) BTA ligands were able to form different self-assemblies including nanospheres via hydrogen bonding templated by sulfate anions. 43 As ZIF-8 has been used as the best candidate for protein encapsulation due to its ease of assembly, biocompatibility, and eventual biodegradation, we tested the applicability of our hollow ZIF-8 colloidosomes for enzyme encapsulation. 29,34 ZIF-8 colloidosomes are excellent candidates due to their hollow interior and microporous shell where different size and charged enzymes can diffuse.…”
Section: Resultsmentioning
confidence: 99%
“…42 More recently, tripodal Nmethylated(1,3,5-benzene-tricarboxamide)-tris(phenylurea) BTA ligands were able to form different self-assemblies including nanospheres via hydrogen bonding templated by sulfate anions. 43 As ZIF-8 has been used as the best candidate for protein encapsulation due to its ease of assembly, biocompatibility, and eventual biodegradation, we tested the applicability of our hollow ZIF-8 colloidosomes for enzyme encapsulation. 29,34 ZIF-8 colloidosomes are excellent candidates due to their hollow interior and microporous shell where different size and charged enzymes can diffuse.…”
Section: Resultsmentioning
confidence: 99%
“…By designing the interactionsb etween multiple anions and ureido groups,itb ecomesp ossible to construct complexs tructured self-assemblies.K ruger and Gunnlaugsson et al reported the construction of two-dimensional anion-layered supramolecular self-assembliesb yt he interaction of tris-urea 31 ( Figure 21) and as ulfate anion. [135] Wu et al realized the construction of at etrahedral cage with at hree-dimensional cavity capable of guest encapsulationb yt he interaction of tripodal hexakis-urea 32 ( Figure 21) and aphosphate anion. [136] One application of an artificial anion receptor is at ransmembrane anion transporter that mimics biological ionc hannels.…”
Section: Intermolecular Hydrogen Bonding Of Urea and Other Speciesmentioning
confidence: 99%
“…can triazole/triazolium based cages, frameworks and grids be assembled using anion coordination? Some of these structures have been assembled using N−H⋅⋅⋅anion templation, [5,67] but the ability of triazole/triazolium scaffolds to incorporate positive charges and/or halogen and chalcogen bonding groups may give rise to more robust architectures with interesting properties. Can the range of reactions catalyzed by triazoles based foldamers be expanded? We note that halogen and chalcogen bonds have been used in organocatalysis, [68–69] and halo/chalcogen‐triazole foldamers may show promise in this regard.…”
Section: Bigger Picture and Conclusionmentioning
confidence: 99%
“…can triazole/triazolium based cages, frameworks and grids be assembled using anion coordination? Some of these structures have been assembled using N−H⋅⋅⋅anion templation, [5,67] but the ability of triazole/triazolium scaffolds to incorporate positive charges and/or halogen and chalcogen bonding groups may give rise to more robust architectures with interesting properties.…”
Section: Bigger Picture and Conclusionmentioning
confidence: 99%